The interfacial tension at the liquid junction of petrol and Sodium dodecyl sulphate solution - Bhattarai, Ajaya; Singh, Man (Journal of Nepal Chemical Society, 2024)
The precise measurements of petrol interfacial tension (IFT) in the presence of Sodium dodecyl sulphate (SDS) at room temperature by Mansingh Survismeter are reported. The concentration of sodium dodecyl sulphate was varied from above and below the critical micelle concentration (CMC) to cover the minimum and maximum concentrations of the investigated surfactant. Petrol was taken from the dealer in Nepal and used without purification. Therefore, when surfactant is added to the system, the surfactant decreases its free energy, thus decreasing its surface tension